Chapter 26: Specialty Asian Vegetable Production in South Florida - Mary L. Lamberts (EDIS)
The term "specialty Asian vegetables" is used herein to designate a group of lesser known vegetables which are primarily Asian in origin. At present, most consumers who purchase these products are either Asian or preparing Asian cuisine. Some may have potential for appealing to a wider range of consumers. This document is HS740, Horticultural Sciences Department, UF/IFAS Extension. Published November 2006.